A highly selective and sensitive fluorescent probe for Cu2+ based on a novel naphthalimide–rhodamine platform and its application in live cell imaging. Issue 18 (24th April 2017) - Liu, Chang; Jiao, Xiaojie; He, Song; Zhao, Liancheng; Zeng, Xianshun
Abstract : A bifluorophore-based ratiometric fluorescent probe has been developed. The probe is cell-permeable and can be used as a FRET-based ratiometric fluorescent probe for lysosomal Cu 2+ imaging in living cells. Abstract : Copper plays important roles in a variety of fundamental physiological processes. At the cell organelle level, aberrant copper homeostasis in lysosomes can lead to various serious diseases. Herein, a bifluorophore-based, lysosome-targetable Cu 2+ -selective ratiometric fluorescent probe (V ) has been synthesized by reasonable design. The probeV shows high selectivity toward Cu 2+ ions over other cations and exhibits high sensitivity (1.45 nM) for the detection of Cu 2+ ions. Meanwhile, the probe is cell permeable and suitable for ratiometric visualization of lysosomal Cu 2+ in the living cell.